Water conservation strategies of large African ungulates - Strauss, Willem Maarten (My University, 2017)
Ecosystems in the southern hemisphere are limited mainly by water availability, a resource predicted to become increasingly scarce in the region in the face of anthropogenic climate change. Understanding how the artiodactyls (e.g., sheep, goats, cattle, antelope and camels), an important grouping of animals regionally, conserve body water to facilitate their survival, is therefore of importance. The idea that selective brain cooling conserves body water has been advanced for more than 20 years, without any definitive proof that ungulates, naturally making use of selective brain cooling, actually save body water as a result of implementing selective brain cooling. Using implanted biologgers I simultaneously measure carotid arterial and hypothalamic temperature in Dorper sheep Ovis aries. The concomitant determination of water turnover, based on the washout rates of the stable hydrogen isotope deuterium oxide (D2O), allowed me to measure the volume of water that a dehydrated Dorper sheep conserves during a day when exposed to heat. Artiodactyls differ in their water requirements though, and may have selective brain cooling capabilities relative to their level of water dependency. I therefore undertook the first comparative investigation into selective brain in free-living artiodactyls by implanting, with the assistance of colleagues, biologgers to measure carotid arterial and hypothalamic temperatures in three large, sympatric artiodactyl species with varying water dependencies. Despite a clear water-dependency gradient across species, I found no difference in the magnitudes of selective brain cooling, iii the proportion of time that selective brain cooling was used, or the threshold temperatures for selective brain between the gemsbok Oryx gazella, red hartebeest Alcelaphus buselaphus or blue wildebeest Connochaetes taurinus in an environment where the animals had free access to water. I found greater variability in selective brain cooling within species, than between species and conclude that all three species had the same underlying ability to make use of selective brain cooling. Artiodactyls, however, are likely to rely on range of water conservation mechanisms in the face of climate change. A variable body temperature and the use of appropriate microclimates are two additional strategies that could be important in the quest to conserve body water. I therefore investigated the 24h nychthemeral body temperature rhythms of the gemsbok, red hartebeest and blue wildebeest, in combination with their 24h microclimate use patterns, during the five months of a southern hemisphere calendar year most challenging physiologically: the end of the dry season through the peak of summer. I found no species differences in the 24h nychthemeral body temperature rhythms of the gemsbok, the red hartebeest or the blue wildebeest. All three species, however, were heterothermic over about the first 50 days of the study, as a result of elevated maximum and depressed minimum body temperatures. Although subtle differences were detected in microclimate use, all three species used behavioural thermoregulation and accessed microclimates cooler than that available in the full sun. Such behaviour was enhanced during the hottest days, compared to the coolest days. In conclusion, I have investigated some of the water conservation strategies relied upon by large African ungulates in their current environments. These strategies are not mutually exclusive and will all benefit these species in the face of climate change. The long-term monitoring of these water conservation strategies will allow us to tease out the relative contributions that selective brain cooling, heterothermy and microclimate use makes to body water conservation and how that translates to individual fitness.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa, 2017
Keywords: Conservation of Water Resources